2021
DOI: 10.1055/s-0041-1740585
|View full text |Cite
|
Sign up to set email alerts
|

Different Doses of Intravenous Tranexamic Acid in Revision Total Knee Arthroplasty: A Retrospective Study

Abstract: Purpose This article assessed the efficacy and safety of different doses of intravenous tranexamic acid (TXA) in revision total knee arthroplasty (TKA). Methods We retrospectively identified 122 patients in our institution who underwent revision TKA with a history of perioperative intravenous TXA utilization. According to the sum of intravenous TXA documented, all patients were divided into three groups: 1 g intravenous TXA, 2 g intravenous TXA, and equal or greater than 3 g intravenous TXA. The prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
(73 reference statements)
1
1
0
Order By: Relevance
“…The results suggest that no significant differences were found between the TXA regimens when assessing hemoglobin reduction (3.4 g/dL in the single-dose IV group and 3.6 g/dL in the double-dose IV group), calculated blood loss ( P = 0.90), or transfusion rates (14% in the single-dose IV group and 18% in the double-dose IV group), whereas according to Kang et al [ 34 ] three doses (3 g) of postoperative IV-TXA reduced blood loss and reduced postoperative inflammation and fibrinolytic reactions more than a single dose (1 g) or two doses (2 g) in elderly patients after TKA without increasing the incidence of adverse events [ 34 ]. A similar observation was made in the Chen et al [ 35 ]; a similar view was reported in the study by Chen et al; a recent randomized controlled trial study showed that [ 33 ] the single-dose regimen was non-inferior compared to the two-dose regimen. Therefore, this meta-analysis will answer the question of whether two-dose versus single-dose intravenous TXA is more effective in terms of total blood loss, transfusion rates, postoperative hemoglobin levels and length of hospital stay, deep venous thrombosis (DVT), and pulmonary embolism (PE), without sacrificing safety.…”
Section: Introductionsupporting
confidence: 83%
“…The results suggest that no significant differences were found between the TXA regimens when assessing hemoglobin reduction (3.4 g/dL in the single-dose IV group and 3.6 g/dL in the double-dose IV group), calculated blood loss ( P = 0.90), or transfusion rates (14% in the single-dose IV group and 18% in the double-dose IV group), whereas according to Kang et al [ 34 ] three doses (3 g) of postoperative IV-TXA reduced blood loss and reduced postoperative inflammation and fibrinolytic reactions more than a single dose (1 g) or two doses (2 g) in elderly patients after TKA without increasing the incidence of adverse events [ 34 ]. A similar observation was made in the Chen et al [ 35 ]; a similar view was reported in the study by Chen et al; a recent randomized controlled trial study showed that [ 33 ] the single-dose regimen was non-inferior compared to the two-dose regimen. Therefore, this meta-analysis will answer the question of whether two-dose versus single-dose intravenous TXA is more effective in terms of total blood loss, transfusion rates, postoperative hemoglobin levels and length of hospital stay, deep venous thrombosis (DVT), and pulmonary embolism (PE), without sacrificing safety.…”
Section: Introductionsupporting
confidence: 83%
“…According to the National Joint Registry, more than 100,000 knee replacements are performed each year in England, Wales and Northern Ireland. Whilst most studies related to the use of TXA in knee surgery have examined blood loss in patients with osteoarthritis, it has proven to be efficacious in patients with rheumatoid arthritis [6], cancer [7] and in revision surgery [8]. Therefore, it seems reasonable to administer TXA to all patients requiring knee arthroplasty, irrespective of their underlying diagnosis.…”
Section: Safety Datamentioning
confidence: 99%